Komodifikasi Musik Resepsi Pernikahan di Bandung - Yudi Permana; Arthur S. Nalan; Indra Ridwan (PANTUN: Jurnal Ilmiah Seni Budaya, 2020)
The term cover here means to re-sing or re-perform a song. The process of covering a song is essentially an adaptation, in which much of the value lies in the cover musician’s interpretation. Covers can easily be found at wedding receptions in the case of performing popular songs and romantic themes. This research studies about pop cover songs on wedding receptions, using commodification theory by Vincent Mosco. Data collection methods are literature studies, interview, and observation. From this research, the results show that the commodification of pop music covers are as follows: (1) commodification of content, cover songs are packaged into a romantic musical performance, as if giving a "message" or “meaning” that a wedding party without musical entertainment would be felt less lively (2) commodification of audiences, the bride as clients are used as a source of economic (3) commodification of labor, skill and service of musicians as workers, are treated as commodities and rewarded in return. Wedding reception as popular culture is closely related to a society prioritizing prestige and image rather than just utilities.Keywords: commodification, cover, wedding music